2006
DOI: 10.1016/s1808-8694(15)30061-6
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and incidence facial fractures in children and adults

Abstract: Accidents with automobiles continue being the main cause of facial trauma, especially of multiple fractures due to the great transmission of kinetic energy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
55
0
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(84 citation statements)
references
References 25 publications
14
55
0
8
Order By: Relevance
“…With regard to the maxillofacial fractures, the most commonly involved bones were the mandible, followed by zygomatic-orbital complex. These reports are consistent with some other literatures [4,7,8], but differ in other study from South Korea [17]. that denotes nasal bone as the most fractured site followed by the mandible.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…With regard to the maxillofacial fractures, the most commonly involved bones were the mandible, followed by zygomatic-orbital complex. These reports are consistent with some other literatures [4,7,8], but differ in other study from South Korea [17]. that denotes nasal bone as the most fractured site followed by the mandible.…”
Section: Resultssupporting
confidence: 92%
“…This study found 83% male and 17% female giving a male-to-female ratio of 4.8:1 which is similar to those reported literature [7,8,14]. Men in the country actively participated during the state of confl ict and mostly involved in other outdoor activities.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…De plus, beaucoup de voitures sont vieilles, et cela est aggravé par les éventuels contrôles techniques de complaisance. Dans la littérature en général, les AVP constituent la première cause des traumatismes maxillo-faciaux [10]. Depuis l'avènement de la ceinture de sécurité, et surtout de l'airbag, les chiffres ont beaucoup diminué, notamment dans les pays développés [11,12].…”
Section: Discussionunclassified
“…%28,3, Afolabi ve ark. %57.5 ile trafik kazalar›n› etyolojide en s›k faktör olarak bildirmekle birlikte (5,14), Erdman ve ark. %36, Fornazieri ve ark.…”
Section: Tartifimaunclassified